Biossorventes na área ambiental: revisando aplicações - Franco, Diego Siqueira (Universidade Federal de São Carlos, 2022)
Concern with water pollution has intensified more and more, since this resource is essential for various activities carried out by man. However, even knowing that this resource is considered finite, the release of untreated effluents has been a result. The main responsible for change in water quality are domestic activities, industrial activities and agro-industrial activities. As well as polluting water, agro-industrial activities are also responsible for high amount of waste generated, which is often improperly disposed off. Faced with the problem involving water pollution, in recent years researchers have sought alternative treatments in removal of pollutants, where biosorption technique has been highlighted, being a process that removes pollutants from aquatic environment using solids of natural origin. Among solids that can be used, we have agro-industrial residues. In this context, the present study aimed to analyze the application of several biosorbents through selected articles in an exploratory and selective way, in order to contribute to the study of biosorption technique. In this way, it was possible to analyze some parameters that influence the technique such as pH, temperature, contact time and stirring speed, reaching the conclusion that all selected articles showed good biosorption capacity and efficiency, but studies with a greater number of parameters and intervals are needed.
Biosorbents in the environmental area: reviewing applications
Keywords: Biossorção; Biossorventes; Resíduos agroindustriais; Biosorption; Biosorbents; Agro-industrial waste; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS